2003
DOI: 10.1046/j.1471-4159.2003.01918.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial peroxiredoxin‐3 protects hippocampal neurons from excitotoxic injury in vivo

Abstract: Mitochondria are involved in excitotoxic damage of nerve cells. Following the breakdown of the calcium-buffering ability of mitochondria, mitochondrial calcium overload induces reactive oxygen species (ROS) bursts that produce free radicals and open permeability transition pores, ultimately leading to neuronal cell death. In the present study, we focused on a mitochondrial antioxidant protein, peroxiredoxin-3 (Prx-3), to investigate the mechanism by which toxic properties of ROS were up-regulated in mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 35 publications
4
88
0
Order By: Relevance
“…Proteome analysis reveals up-regulation of PRX1 and PRX6 in experimental models of familial amyotrophic lateral sclerosis (66,67). Using both in vivo and in vitro models of excitotoxic injury, two independent studies indicate that overexpression of PRX3 or PRX5 provides a certain degree of neuroprotection in these models (68,69), thereby providing evidence for the involvement of certain isoforms of PRX in the progression of neurodegenerative disorders. However, none of these studies showed generation of the oxidized forms of PRX.…”
Section: Discussionmentioning
confidence: 99%
“…Proteome analysis reveals up-regulation of PRX1 and PRX6 in experimental models of familial amyotrophic lateral sclerosis (66,67). Using both in vivo and in vitro models of excitotoxic injury, two independent studies indicate that overexpression of PRX3 or PRX5 provides a certain degree of neuroprotection in these models (68,69), thereby providing evidence for the involvement of certain isoforms of PRX in the progression of neurodegenerative disorders. However, none of these studies showed generation of the oxidized forms of PRX.…”
Section: Discussionmentioning
confidence: 99%
“…A down-regulation of Prx-3 has been described in various experimental models that are characterized by an increased cellular oxidative stress [153][154][155]. In human heart failure Brixius et al [156] have also reported a selective down-regulation of the mitochondrial Prx-3 and Prx-5 as well as that of the extracellular Prx-4 isoform and that of the cytosolic Prx-6, while the cytosolic Prx-1 and Prx-2 isoforms are unaffected by the enhanced ROS production.…”
Section: Down-regulation Of Peroxiredoxin-3 Expression By Angiotensinmentioning
confidence: 99%
“…7 Furthermore, in vivo transfer of the Prx-3 gene protected neurons against cell death induced by oxidative stress. 8 These beneficial characteristics make Prx-3 an important candidate for therapy against LV failure after MI, in which ROS production has been demonstrated to be increased within the mitochondria. 1,4 Although several previous reports showed the beneficial effects of antioxidants on heart failure, 9,10 no study has ever been performed to specifically examine the protective role of Prx-3.…”
Section: Clinical Perspective P 1786mentioning
confidence: 99%